Fast frequency response for effective frequency control in power systems with low inertia. Issue 16 (12th December 2018) - Hong, Qiteng; Nedd, Marcel; Norris, Seán; Abdulhadi, Ibrahim; Karimi, Mazaher; Terzija, Vladimir; Marshall, Benjamin; Bell, Keith; Booth, Campbell
Abstract : The increasing penetration of renewable generation has led to the decrease of power systems' overall inertia, which introduces significant challenges to frequency stability. In this paper, the potential of using Fast Frequency Response (FFR) to enhance frequency control in power systems with low inertia is investigated in detail. A Generic System Frequency Response (GSFR) model taking into account of the penetration level of Non‐Synchronous Generation (NSG) and FFR has been developed and used to investigate the impact of reduced inertia on frequency control and demonstrate that the amount of reserve power to be scheduled can be significantly reduced with the deployment of FFR. The impact of the different FFR resources' characteristics (e.g. response delay, ramp rate, etc.) on the effectiveness of frequency control is also investigated, based on which the desirable specifications for FFR schemes are summarised. These desirable properties of FFR schemes are taken into account in the design of a wide‐area monitoring and control system termed 'Enhanced Frequency Control Capability (EFCC)', which is proposed for the delivery of FFR in the future Great Britain transmission system. The design and operation of the EFCC scheme are presented, along with a case study demonstrating its effectiveness in enhancing the frequency control.